IDENTIFIKASI KEBERADAAN BUNKER DENGAN METODE GEOLISTRIK TAHANAN JENIS KONFIGURASI WENNER ALPHA DAN DIPOLE-DIPOLE - Adawiyah, Robiatul; Supriyanto, Supriyanto; Natalisanto, Adrianus Inu (GEOSAINS KUTAI BASIN, 2018)
Bunker existence in Jembayan Village of Loa Kulu subdistrict, Kutai Kartanegara regency, was identified by using geoelectric method with configurations of Wenner Alpha and Dipole-Dipole. The bunker area was located at the zone of 50 UTM with UTM’s coordinate position, namely: UTM X 0502449 and UTM Y 9939205, consisting of 7 measurement points using 2 configuration, i.e.: Wenner Alpha configuration and Dipole-dipole configuration. The length of each measuring point is 72 m, using spaces between 1.5 m electrodes and the distance from each measuring point is 5 and 10 m. From the research results it was obtained the cross-section of inversion from Res2DINV which describes the existence of bunker. The cross-section of the inversion related to the resistivity ranging from 2.888 Ωm to 9.103 Ωm indicated the resistivity values of the underground bunker area. On the path of all measurement points (path A, B, C, D, E, F, G) there was an indication of bunker with different resistivity values.